USEFUL LEXICON KNOWLEDGE OF ESL BEGINNER - Abdulmalik Usmana; Dahiru Musa Abdullahib (International Scientific and Current Research Conferences, 2021)
The paper tries to research the degree of useful information on ESL students, the composing quality and the connection between the jargon information and the composing quality. 150 last year understudies of English language in a college in Nigeria were haphazardly chosen as respondents. The respondents were approached to compose an exposition of 300 words inside 60 minutes. The articles were composed into Vocab Profiler of Cobb (2002) and broke down the Lexical Frequency Profile of the respondents. The articles were additionally surveyed by autonomous inspectors utilizing a standard rubric. The discoveries uncover that the degree of useful jargon knowledge of the respondents is restricted. The composing nature of most of the respondent is reasonable and there is a critical connection among's jargon and the witting nature of the subjects. The analysts set that useful jargon is the indicator of composing quality and suggest different methods through which instructing and learning of jargon can be improved.